2015
DOI: 10.1177/0032885515596520
|View full text |Cite
|
Sign up to set email alerts
|

Making Fatty Girl Cakes

Abstract: This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cells-all to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Many women mentioned that, when at homes, they would cook food, which they thought had beneficial effect on health. A similar idea has been found in earlier studies that showed that perceptions toward food in prisons also redefine how people "read" their bodies and reconstruct notions of "good" and "healthy" (Smith, 2002(Smith, , 2009Smoyer, 2015aSmoyer, , 2015b. In the prisons under study, food was often assessed in terms of nutritional and medicinal values.…”
Section: Experiencing Food In Relation To Healthsupporting
confidence: 61%
See 1 more Smart Citation
“…Many women mentioned that, when at homes, they would cook food, which they thought had beneficial effect on health. A similar idea has been found in earlier studies that showed that perceptions toward food in prisons also redefine how people "read" their bodies and reconstruct notions of "good" and "healthy" (Smith, 2002(Smith, , 2009Smoyer, 2015aSmoyer, , 2015b. In the prisons under study, food was often assessed in terms of nutritional and medicinal values.…”
Section: Experiencing Food In Relation To Healthsupporting
confidence: 61%
“…In her work with Canadian male prisoners, Godderis (2006a) showed how they assert their identity through adaptations and oppositions as individuals or in groups using food as a medium of resistance and self-reclamation (Godderis, 2006;see Collins, 2004). Smoyer (2015aSmoyer ( , 2015b, in her study of formerly imprisoned women in the United States, shows how small acts of resistance to prison dictates such as smuggling from the cafeteria and kitchen or cooking in the cells were some ways of how inmates (re)created food for themselves. Despite constraints, the food space in prison has, thus, been perceived as an arena where identities as prisoners are reworked upon at personal or group level and considerable struggles revolve.…”
Section: Discussionmentioning
confidence: 99%
“…And you pour the milk over and eat it that way, it's good that way.” These examples, while the minority of participant experiences, nevertheless show that certain participants took a positive approach to the provided prison diets, and that work assignments provided access to food and autonomy over the quantity consumed. The ingenuity of ‘hacking’ prison food items into meals that are edible has been cited in the literature as a method of resisting the prison's assault on individuality and its attempt of total corporeal control (Smoyer, 2016).…”
Section: Food As Corporeal Power: Hunger Degradation and Disciplinementioning
confidence: 99%
“…Despite its centrality to prison conditions and experience, prison food has received relatively little academic attention. Existing scholarship has investigated important relationships between food, health, and identity; ways in which poor-quality food causes feelings of unworthiness and neglect; food as pleasure, punishment, and resistance; the role of food in articulations of masculinity and ethnicity; as well as the role of food in prisoner organizing (de Graaf and Kilty, 2016;Einat and Davidian, 2019;Godderis, 2006aGodderis, , 2006bSexton, 2015;Smith, 2002;Smoyer, 2016;Ugelvik, 2011). As well, we have seen how non-white prisoners in Norway are normalized through national diets, and how the British government's self-proclaimed cultural sensitivity is undermined in Immigration Removal Centers by its serving of a 'British' diet (DeAngelis, 2020;Ugelvik, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Explorations of life inside women's correctional institutions have described relationships among incarcerated people, interactions with staff, health care access and utilization, and experiences of interpersonal and structural trauma (Ahmed et al, 2016;Fowler et al, 2010;Severance, 2005;Wright et al, 2012). Daily activities related to food and eating, employment, communication with nonincarcerated friends and family, and education have been explicated (Collica-Cox, 2014;Michalsen et al, 2010;Richmond, 2014;Smoyer, 2016). Analysis has described the impact of the carceral setting on women's constructions of identity, power, and rehabilitation (Bosworth, 2017;McCorkel, 2017;Rowe, 2011).…”
Section: Introductionmentioning
confidence: 99%